Teachers' perspectives of what works: Implementation of AT for students with disabilities. Issue 3 (4th May 2022) - Chambers, Dianne; Jones, Phyllis; Reese, Lori; Wilcox, Catherine
ABSTRACT: Assistive technology (AT) can be used to support the academic and social development of students with disabilities in the classroom. This research asked teachers of students with disabilities to share the elements that they report as being necessary for the successful implementation of assistive technology they have available in their classrooms. The teachers reported on their successful experiences. There has been a great deal of research in the appropriate selection of devices to suit the needs of the individual student and their environment. While the successful implementation and incorporation of the AT into the classroom have been researched, it has emerged from this research that teachers are not utilizing commonly identified implementation checklists/processes. A number of key successful elements were identified, such as training, time to plan and respond, using AT effectively, the effort/experience of the teacher, and external support available. Each of these elements is discussed along with suggestions for a simplified implementation process. It should be noted that specific disabilities and assistive technologies were not a focus of the study. Future directions for research in the area of AT implementation are indicated.